2020
DOI: 10.11648/j.ijsqa.20200601.12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Harvesting Methods on Storage Behaviour of Mandarin (<i>Citrus Reticulata</i> Blanco) Under Cellar Condition

Abstract: Mandarin (Citrus reticulata Blanco) is a premier fruit crop expanding rapidly in the hilly areas of Nepal. Most of the mandarin growers in Nepal are using conventional harvesting method which is responsible for deteriorating the fruit quality and shortening the postharvest shelf life. Thus, this experiment was conducted to evaluate the effect of different harvesting methods on quality and shelf-life of mandarin during storage under the Cellar condition (11±2°C and 85-90% RH). For this, mandarin fruits harveste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Previous studies on the effect of harvesting methods on the storage behavior of fruits support our findings. For instance, a recent study by Rokaya et al (2020) evaluated mandarin storability under cellar condition and reported less water loss in clipped fruits (3.15%) than that of fruit harvested by sticks (15.81%) (Rokaya et al, 2020). As well a study, reported a weight loss of 18-21% in fruit stored at room temperature for 12 days (Purbiati and Supriyanto, 2013).…”
Section: Physiological Loss In Weight (Plw)mentioning
confidence: 96%
See 4 more Smart Citations
“…Previous studies on the effect of harvesting methods on the storage behavior of fruits support our findings. For instance, a recent study by Rokaya et al (2020) evaluated mandarin storability under cellar condition and reported less water loss in clipped fruits (3.15%) than that of fruit harvested by sticks (15.81%) (Rokaya et al, 2020). As well a study, reported a weight loss of 18-21% in fruit stored at room temperature for 12 days (Purbiati and Supriyanto, 2013).…”
Section: Physiological Loss In Weight (Plw)mentioning
confidence: 96%
“…In contrast, lower rot incidence in SE and CH treatments is attributed to intact fruit with controlled sap oozing and lateral infection due to the presence of pedicel in fruit (Singh et al, 1993;Sonkar et al, 1999;Kumargoud et al, 2017). Moreover, fruits with intact stalk were less prone to fungal infection during storage than those without fruit stalk (Rokaya et al, 2020;Purbiati and Supriyanto, 2013;Waskar et al, 1997). Likewise, twisting, turning action by the three soft rubber padded claws of LRF prevents peeling and damage of outer skin around peduncle extremity point.…”
Section: Rot Incidence (Decay Loss) and Shrinkage Behaviormentioning
confidence: 99%
See 3 more Smart Citations